2018
DOI: 10.1080/20002297.2018.1557986
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome sequencing-based strain-level and functional characterization of supragingival microbiome associated with dental caries in children

Abstract: Studies of the microbiome associated with dental caries have largely relied on 16S rRNA sequence analysis, which is associated with PCR biases, low taxonomic resolution, and inability to accurately study functions. Here, we employed whole metagenome shotgun sequencing, coupled with high-resolution analysis algorithm, to analyze supragingival microbiomes from 30 children with or without dental caries. A total of 726 bacterial strains belonging to 406 species, in addition to 34 bacteriophages were identified. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 64 publications
6
40
0
7
Order By: Relevance
“…have been associated with both health and dental caries, depending on the study. Our findings are in line with several studies that associated Prevotella with dental caries (21, 5961), including one that found it was the best predictor of childhood caries (59). These reports were in contrast to a study where Prevotella were enriched in the healthy cohort (62).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…have been associated with both health and dental caries, depending on the study. Our findings are in line with several studies that associated Prevotella with dental caries (21, 5961), including one that found it was the best predictor of childhood caries (59). These reports were in contrast to a study where Prevotella were enriched in the healthy cohort (62).…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that S. mutans, when present, has a large influence on the pathogenicity of the oral microbiome due to its prodigious capacity to generate insoluble glucans and resultant biofilms (9, 26). Other oral microbiome studies have found S. mutans at low abundances (20, 21, 54), and the use of saliva in this study may explain its rarity, and possibly underestimation, here—as an exceptional biofilm-former, it is less likely to be shed from its dental plaque residence into the salivary milieu (55).…”
Section: Discussionmentioning
confidence: 59%
“…We have recently used whole metagenome sequencing (WMS) to study the supragingival microbiome in 30 children with various levels of carious severity [9]. In WMS, all fragments of DNA in a sample are sequenced, which allows exploring the different categories of microorganisms present in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA isolation method, hereafter referred to as the "MetaSUB method", was developed for the MetaSUB Consortium (www.metasub.org) to complement an ongoing global effort to characterize subway and urban environment microbiomes using surface swab samples, by extending the effort to also include air samples. The MetaSUB method was benchmarked against two other state-ofthe-art DNA isolation methods: a custom multicomponent DNA isolation method developed for use in aerosol microbiome research published by Jiang et al [28], and the commercial ZymoBIOMICS DNA Microprep Kit commonly used in environmental microbiome studies [38][39][40][41]. The performance of the three DNA isolation methods was evaluated using both a mock microbial community and real-world low biomass subway air samples.…”
Section: Introductionmentioning
confidence: 99%